Digital övervakning i arbetslivet - en rättslig balans mellan arbetsledningsrätt och personlig integritet - Andersson,Frida (2026)
Abstract This thesis examines digital surveillance in working life and analyses the limits of the employer’s managerial prerogative and right of control in relation to the employee’s right to personal integrity. The purpose of the thesis is to analyse the legal framework governing surveillance in the workplace and to explain how the balance between control and integrity is maintained in a digitalised working environment, with particular focus on Swedish law and EU law. Research question: How is the employer’s managerial and supervisory authority balanced against the employee’s right to personal integrity in the context of digital workplace surveillance, and what legal protection is provided by Swedish law, EU law, the GDPR and the AI Act in this regard? The thesis maps the legal protection provided to individuals and highlights how a complex EU legal framework limits the employer’s scope for digital control measures through requirements of proportionality, transparency and human oversight. Control measures may be permitted for legitimate purposes, such as security or technical needs, for example through monitoring of digital communications. At the same time the GDPR and the AI Act impose clear limits, real-time surveillance and behavioural monitoring are, as a general rule, not permitted. Less intrusive alternatives must always be chosen and employees must be clearly informed of any monitoring. The legal framework strengthens the protection of employees’ personal integrity in the digitalised workplace, without forming an absolute barrier to control measures that are necessary in relation to a legitimate purpose. Keywords: Digital surveillance, Labor law, Personal integrity, GDPR, AI-Act, EU-law.
Keywords: Digital övervakning; Arbetsledningsrätt; Personlig integritet; GDPR; AI-förordningen; Arbetsrätt; EU-rätt.